2015
DOI: 10.1097/aln.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Outcomes of Substance Use Disorder among Anesthesiology Residents

Abstract: Background The goal of this work was to evaluate selected risk factors and outcomes for substance use disorder (SUD) in physicians enrolled in anesthesiology residencies approved by the Accreditation Council for Graduate Medical Education. Methods For each of 384 individuals with evidence of SUD while in primary residency training in anesthesiology from 1975–2009, two controls (n=768) who did not develop SUD were identified and matched for gender, age, primary residency program, and program start date. Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…7 It has been suggested that anesthesia providers are at increased risk for substance abuse relative to other medical specialties as a result of high levels of work-related stress, easier access to controlled substances, chronic exposure to trace quantities of addictive substances, and a variety of other potential contributing factors. 8,9 Additionally, previous reports have indicated that anesthesiologists are overrepresented in drug treatment programs relative to their proportion among medical specialties and are more likely to abuse substances with a higher risk of relapse. 2,10,11 In addition to anesthesiology, other specialties, such as family medicine, internal medicine, and surgery, are overrepresented when compared with obstetrics and gynecology or pediatrics.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…7 It has been suggested that anesthesia providers are at increased risk for substance abuse relative to other medical specialties as a result of high levels of work-related stress, easier access to controlled substances, chronic exposure to trace quantities of addictive substances, and a variety of other potential contributing factors. 8,9 Additionally, previous reports have indicated that anesthesiologists are overrepresented in drug treatment programs relative to their proportion among medical specialties and are more likely to abuse substances with a higher risk of relapse. 2,10,11 In addition to anesthesiology, other specialties, such as family medicine, internal medicine, and surgery, are overrepresented when compared with obstetrics and gynecology or pediatrics.…”
Section: Résumémentioning
confidence: 99%
“…1 Traditionally, opioids have been the most commonly abused anesthesia medication by anesthesia care providers (ACPs). 1,9,13 Previous reports have documented opioids as the substances abused in 62% 9 and 66% 13 of cases. Nevertheless, non-opioid anesthesia medications also represent a significant source of abuse and are a potentially underappreciated cause of morbidity, mortality, and professional demise among ACPs.…”
Section: Résumémentioning
confidence: 99%
“…3,4 The most divergent result in Australasia, however, has been the high incidence of propofol abuse, particularly over the last decade. In the most recent ten-year survey of Australasian anaesthetists, 61 cases were reported, an incidence of 1.2 cases per 1,000 anaesthetist years.…”
Section: To the Editormentioning
confidence: 99%
“…3 Those with SUD were 15 times more likely not to complete their training, ten times more likely not to become Board (ABA) certified, and seven times more likely to have adverse medical licensure actions. The risk of death after training was 7.9 times higher in the SUD cases.…”
mentioning
confidence: 99%
“…2 The analysis for that study integrated anonymized data from the American Board of Anesthesiology (ABA), the National Death Index, and the Disciplinary Action Notification Service of the Federation of State Medical Boards. The overall incidence of SUD during anesthesia training was 0.86%, with 384 SUD cases identified.…”
mentioning
confidence: 99%